The Effectiveness of Contextual Redefinition Strategy on Reading Comprehension of Descriptive Text of The Tenth Grade Students of MAU Darul Hidayah BenelanLor in the Academic Year 2019/2020 - Dwi Novitasari; Tri Mulyati; Sutami Dwi Lestari (LUNAR, 2020)
The purpose of this research was to know whether the students taught by using Contextual Redefinition Strategy get better on Reading Comprehension of Descriptive text score. This reserach was an experimental research. The type of the research was a pre experimental reserach. The researcher used one group pretest and posttest design. The respondents of this research was 21 students. Before giving the treatment, the students were given pre-test, and post-test was given after the treatment. The technique of collecting data was a test. The technique of data analysis was T-test formula in order to know the difference between the average of posttest of experimental class and pretest of experimental class. After having calculated the T-test. T-test was anlyzed and interpreted with the degree of significances 5% with db = 19 and the T-table is 2,093. The results of T-test analysis is 9,96. It means that the T-test ( 9,96 ) is higher than T-table ( 2,093 ) in the significances 5%. From the research finding, it can be concluded that the students taught by using contextual redefinition strategy get better score on reading comprehension of descriptive text. It is suggested for the teachers and the students to use this strategy in teaching reading comprehension because this strategy is very useful to improve students vocabulary. For further researcher to conduct further research on similar area by improving the methodology.